New high-selective and sensitive extraction-photometric method for determination of cobalt - Kachanovich, Iryna V.; Yagorau, Uladzimir V.; Rakhmanko, Yauheni M. (Journal of the Belarusian State University. Chemistry, 2017)
Anion-exchange extraction of thiocyanate complexes of zinc, cobalt(II), copper(II), cadmium, mercury(II), nickel with N,N-didecyl-N-[2-(didecylamino)ethyl]-decan-1-aminium picrate in different solvents has been investigated. Toluene, decane, octane, chloroform and carbon tetrachloride were used as solvents. The conditional exchange constants of picrate and thiocyanate ions to thiocyanate complexes of mentioned above metals are obtained. It is found that decane and octane are the best solvents for the extraction of cobalt(II) thiocyanate complexes. The simple high-sensitive and express method for determination of cobalt(II) has been proposed. The method is based on quantitative extraction of cobalt(II) from 0.1 mol /l thiocyanate background solution and measuring the extract absorbance at either 630 or 325 nm. 100-fold preconcentration is possible. The range of cobalt(II) concentration to be determined is 0.1– 4.0 ppm without pre-concentration and 1.0 – 40.0 ppb with pre-concentration. The determination error is not more than 3 % rel. without pre-concentration and not more than 12 % rel. with pre-concentration. 1000-fold excess of nickel, cadmium, manganese(II), lead(II), chrome(III), ferrum(II), as well as magnesium, calcium, barium, potassium, sodium, lithium does not affect cobalt determination.